Historiography of Rock Art Studies from the Guanacaste Mountain Range and its Coastal Plain in northwest Costa Rica - Costa, Philippe; Molina Muñoz, Priscilla; Künne, Martin; Gelliot, Eric (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2023)
The rock art in Costa Rica has been the subject of particular studies since the end of the 19th century, being at first the topic of punctual documentations that followed casual discoveries. Despite the systematic registries developed between the 1960s and 1970s, in the Guanacaste Mountain range, located in the northwest of the country, there was no intensification of scientific research before the 1990s. Therefore, the thematic study of this group of archaeological sources is still a relatively recent phenomenon. Following and analysing the thread of the publications on the rock art of the Guanacaste mountains range, one can see how the contexts, questions, analytical approaches, and applied techniques have shaped the knowledge and interpretation of the representations studied in a transcultural region between Mesoamerica and the Intermediate Area.